New Town planning in Hong Kong: The case of Sha Tin - Chan, Ka Lok (International Planning History Society Proceedings, 2024)
Previous narratives suggested that Sha Tin New Town was the model New Town in Hong Kong. This study looks at its formation process from the perspective of planning politics, and unravels that how colonial power dynamic between multiple politico-economic interests exerted influence towards planning ideas and built environment of Sha Tin and its later New Town. After examining archival documents and other materials, it unmasks the shifting rationales of urbanising Sha Tin from socioeconomic-oriented to political-oriented. The drivers of landscape transformation evolved from local-led, ad-hoc government-led to mainly government-led. Based on various contextual and temporal constraints, planning officials skilfully shaped a high-density urban form of Sha Tin New Town and attempted to evolve the nature of New Town to achieve strategic objectives of colonial government. Meanwhile, exploring shifting priorities of land use within New Town could unmask official priorities of New Town development and urbanisation strategies. Additionally, this study based on declassified archival material could offer a historical and narrative-driven account to fill research gap of New Town formation in post-war Hong Kong.